UJI AKTIVITAS ANTIMIKROBA HASIL FRAKSINASI EKSTRAK ETANOL DAUN PATIKALA (ETLINGERA ELATIOR) TERHADAP BEBERAPA MIKROBA UJI - Faridha Yenny Nonci; A Tenriugi Daeng; Hasnia A (Jurnal Farmasi UIN Alauddin Makassar, 2016)
The purpose of this study was to determine the activity of ethanol extract of leaves patikala fraction (Etlingera elatior) as an antimicrobial in some microbes and identify the components of compounds in the leaves patikala which acts as an inhibitor of the microbes. The research was done by using KLT-Bioautografi. Simplicia leaves patikala macerated with maceration method stratified by using solvent n-hexane and ethanol 96%, then the test screening of bacteria which then extract fractionation actively performed by the method of KCV (Vacuum Liquid Chromatography), chromatographic separation of compounds results then carried TLC -Bioautografi are placed on the surface of the solidified medium. After 15-30 minutes plates (chromatogram) is appointed and removed from the medium, were incubated for 1 x 24 hours at 37 ° C for bacteria and 3 x 24 hours at room temperature for mushrooms. Results showed that the microbes could be reversed after tested KLT- Bioautografi there are 5 bacterium is Escherichia coli, Bacillus subtilis, Staphylococcus aureus, Streptococcus mutans, and Pseudomonas aeruginosa. Further quantitative research to determine the level of effectiveness of the results of the leaf fraction patikala to determine the value of MIC (Minimum Inhibitory Concentration) and the sensitivity of the most active fraction against microbes Escherichia coli, Bacillus subtilis, Staphylococcus aureus, Streptococcus mutans, and Pseudomonas aeruginosa.